Olfactory epithelium structure of newt cristate laurenti, 1768 (Amphibia: Caudata) - Stepanyuk, Ya. V.; Motuziuk, O. P.; Степанюк, Я. В.; Мотузюк, О. П. (My University, 2010)
The olfactory capsules structure of the mature Trturus Cristatus (Amphibia, Caudata) individual was explored using morphological methods and method of light microscopy. It was shown, that basic olfactory epthelium receptor cells are placed in clusters which are divided by respiratory cells. Vomeronasal organ is found in lateral part of olfactory capsule. On our opinion, this differentiation of newt cristate peripheral olfactory analyzer comparatively with the fishes is related with transition from aquatic to terrestrial life.
Будова нюхового епітелію тритона гребінчастого
Keywords: amphibian; olfactory analyzer; olfactory capsule; vomeronasal organ; земноводні; нюховий аналізатор; нюхова капсула; вомероназальний орган